PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL - Evans Manurung; Dul Muid (Diponegoro Journal of Accounting, 2015)
This study aimed to analyze the effect of firm characteristics, namely board size, foreign ownership, firm size, profitability, and leverage of board disclosure of corporate social responsibility.The population of this research is manufacturing company listed on the Indonesia Stock Exchange during 2011-2013. Sampling by using purposive sampling method, samples obtained amounted to 162 companies. Types of data used are secondary data with the method of documentation and literature method. The analytical tool used is multiple regression. This study found that board size and foreign ownership has a positive effect on disclosure of corporate social responsibility. However, firm size, profitability and leverage did not effect on disclosure of corporate social responsibility.